Pengajian dan Transformasi Sosiokultural dalam Masyarakat Muslim Tradisionalis Banjar - Alfisyah Alfisyah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2009)
Pengajian is a kind of Islamic preaching which has been found in traditional Muslim community in Banjar, SouthKalimantan. Pengajian is the origin of the emergence of Islamic boarding school (pesantren). Even though pesantren hasalready developed so fast, pengajian can keep its existence in Banjar traditional Muslim community. It even functions as aninstitution which can be dinamics and motivator of the sociocultural transformation in the society